2000
DOI: 10.1016/s0002-9440(10)64980-2
|View full text |Cite
|
Sign up to set email alerts
|

Viruses, Immunity, and Cancer: Lessons from Hepatitis B

Abstract: Address reprint requests to Francis V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
229
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(234 citation statements)
references
References 105 publications
5
229
0
Order By: Relevance
“…The molecular mechanisms that underlie the pathogenesis of inflammation-associated cancer are complex, and involve both the innate and adaptive immune systems 3,133,134,135 . Although viral oncogenes can contribute directly to neoplastic transformation, neither infection nor pathogen-encoded oncogenes are required for inflammatory cells to induce cancer 136 . Indeed, highly reactive chemical compounds, including superoxide, hydrogen peroxide, singlet oxygen and nitric oxide are released from activated phagocytic inflammatory cells of the innate immune system, and can cause oxidative or nitrosative damage to DNA in the epithelial cells, or react with other cellular components such as phospholipids, initiating a free-radical chain reaction 2 .…”
Section: Box 1 | Molecular Mechanisms Of Inflammation-induced Cancersmentioning
confidence: 99%
“…The molecular mechanisms that underlie the pathogenesis of inflammation-associated cancer are complex, and involve both the innate and adaptive immune systems 3,133,134,135 . Although viral oncogenes can contribute directly to neoplastic transformation, neither infection nor pathogen-encoded oncogenes are required for inflammatory cells to induce cancer 136 . Indeed, highly reactive chemical compounds, including superoxide, hydrogen peroxide, singlet oxygen and nitric oxide are released from activated phagocytic inflammatory cells of the innate immune system, and can cause oxidative or nitrosative damage to DNA in the epithelial cells, or react with other cellular components such as phospholipids, initiating a free-radical chain reaction 2 .…”
Section: Box 1 | Molecular Mechanisms Of Inflammation-induced Cancersmentioning
confidence: 99%
“…A series of investigations of the mechanisms by which Tcells control HBV replication showed the major role of cytokine-mediated, intracellular inactivation of HBV that does not require cell death. 8 This noncytolytic antiviral effect, first demonstrated in an HBV transgenic mouse model and subsequently in other animals, is primarily mediated by interferon-gamma (IFN-␄). [9][10][11] A detailed analysis of HBV clearance during acute infection in chimpanzees showed that the disappearance of viral DNA from the liver coincides with IFN-␄ induction before the increase of serum alanine aminotransferase (ALT), in other words, without destruction of hepatocytes.…”
Section: H Epatitis B Virus (Hbv) Is a Noncytopathic Dnamentioning
confidence: 99%
“…Resolution of acute infection is associated with a vigorous polyclonal helper (Th) and cytotoxic T lymphocyte (CTL) response to multiple viral antigens in the infected livers [2,10,62,63]. Moreover, although destruction of virally infected hepatocytes is evident during the resolution of acute infection, it has been elegantly demonstrated that the noncytolytical reduction of viral gene products in infected cells by cytokines, such as interferon gamma and tumor necrosis factor, released from activated T lymphocytes is likely to play an important role in terminating the infection [12,64].…”
Section: Immunological Basis Of Chronicitymentioning
confidence: 99%